Assessment of the effects of UV-A exposure on the mechanical strength of offshore mooring multifilaments - Daniel Magalhães da Cruz; Felipe Tempel Stumpf; Jakson Manfredini Vassoler; Carlos Eduardo Marcos Guilherme (Acta Polytechnica)
The offshore industry faces significant challenges in the dynamic energy and maritime domain, necessitating robust engineering solutions for mooring systems. This study investigates the impact of ultraviolet radiation A (UV-A) on the mechanical strength of high-strength multifilaments, crucial for offshore mooring. Five fibre types: Aramid, High-modulus polyethylene (HMPE), Liquid crystal polymers (LCP), Polyamide and Polyester, are exposed to UV-A for up to 28 days. Initial mechanical characterisation provides baseline data, while subsequent tests reveal varying degrees of degradation. Polyamide and polyester exhibit superior stability, while Aramid and HMPE show restrained degradation. LCP experiences substantial degradation. Mathematical modelling reveals distinct degradation patterns, emphasising the need for comprehensive understanding in ensuring the safety and efficiency of offshore operations. There are indications that degradation by ultraviolet exposure for Aramid, HMPE, polyamide, and polyester fibres, restricts the constitutive behaviour in terms of strength and extension, but without changing the shape of the curve. These findings provide valuable insights for the offshore industry and guidance future research and development efforts.